A new method of sutureless microvascular anastomoses using a thermosensitive poloxamer and cyanoacrylate: An experimental study. Issue 4 (17th January 2015) - Qassemyar, Q.; Michel, G.
<x xml:space="preserve">Abstract</x> Introduction Recently, a new method of sutureless micro‐anastomosis based on the injection of a termosensitive poloxamer into the vessel lumen and application of cyanoacrylate, was described. The long‐term results in animals are attractive but its use requires a specific heated poloxamer gel and an external heating lamp to maintain the surgical site above the transition temperature. The aim of our study was to prove the feasibility of this method of sutureless anastomosis with a poxolamer gel, which could be used at ambient temperature. Materials and Methods Twenty male Sprague–Dawley rats were used. Right common iliac arteries anastomoses (RCIA) were performed with the sutureless method (poloxamer gel and cyanoacrylate) (SG group) and were compared to left common iliac arteries (LCIA) sutured with conventional sutures (CG group). Diameters, duration of microvascular anastomosis (DMA) and patency rates were reported. Results The mean diameter of RCIA and LCIA was about 1 mm. The mean DMA for the SG group was 9.25 ± 1.45min and 21.65 ± 2.96 min in the CG group. Patency rates didn't differ between the both groups, either 15 min after anastomosis (CG group 95% vs.SG group 100%, P = 0.23) or 15 days after surgery (CG group 90% vs.SG group: 95%, P = 0.55). Histological analysis showed lower foreign body reaction in sutureless group. Conclusion This sutureless method of micro‐anastomosis seems to be easy to learn and require lower time than conventional sutures. However, this technique needs further investigations over the coming years to prove long‐term reliability. © 2015 Wiley Periodicals, Inc. Microsurgery 35:315–319, 2015.